2001
DOI: 10.1103/physrevlett.87.179703
|View full text |Cite
|
Sign up to set email alerts
|

Bratkovsky and Levanyuk Reply:

Abstract: Bratkovsky and Levanyuk Reply:The main new result of our paper [1] is that the ferroelectric (FE) with the dead layer of thickness d is always split into domains, no matter how thin the layer is. We have found that the width of the domains a depends exponentially on d 22 when the dead layer is thin. We have also evaluated the response of the structure to external field (Fig. 2 in [1], and Ref. [2]). In the Comment [3] Tagantsev has tried to interpret our approximate Eq. (14), which he misrepresented as the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
349
4
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(370 citation statements)
references
References 4 publications
(9 reference statements)
15
349
4
2
Order By: Relevance
“…In very thin films the interaction between the two opposite surfaces [35], dead layers [36,37] or ferroelastic effects [38][39][40] can induce a departure from LLK, often in the form of a divergence in domain size for very small thickness. On the other hand, experimentally, for perovskite ferroelectrics the LLK holds down to smaller thickness than those studied here (Fig.…”
Section: -2 Value Ofmentioning
confidence: 99%
“…In very thin films the interaction between the two opposite surfaces [35], dead layers [36,37] or ferroelastic effects [38][39][40] can induce a departure from LLK, often in the form of a divergence in domain size for very small thickness. On the other hand, experimentally, for perovskite ferroelectrics the LLK holds down to smaller thickness than those studied here (Fig.…”
Section: -2 Value Ofmentioning
confidence: 99%
“…21 , 22 Formation and stability of 90° domain structures in epitaxial films of ferroelectricinsipient ferroelastic under the misfit strain influence were considered by different groups, with special attention to the period and conditions of existence 23,24,25 and transition between monodomain and polydomain structures. 26 However, the details of domain walls structure were not considered in these studies. Domain walls structure in proper ferroelastic was considered by Salje et al 27 , 28 , 29 It was found 28 that nonzero internal stress exists at a domain wall due to coupling between primary order parameter (shear strain) and dilatation strains there.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, polarization and/or elastic strain in the multidomain state are typically considered using harmonic function approximation, 2,13,26 which is indeed reasonable near the phase transition point, but this approximation could not allow one to grasp the domain walls details for the case of developed domain structure. In contrast, in the paper we derive the domain wall profile near the surface self-consistently using perturbation theory.…”
Section: Introductionmentioning
confidence: 99%
“…In this case the linear response of 180 0 domain structure without pinning is not affected by intimate contact between the ferroelectric and the dead layer (excluding mere renormalization of materials constants by homogeneous stresses). Note that this is invalid in the case of 90 o domains [8] or a linear coupling between the strain and the polarization [9]. Here we address the anomalous behavior of the dielectric constant ǫ ef f in detail.…”
mentioning
confidence: 99%